(untitled) (Research, Society and Development, 2020)
This study aimed to know the expectations of transsexual men regarding the process of cross-sex hormone therapy, analyzing nursing contributions to health care. This study is justified in view of the collaboration of nursing to reduce discrimination and violence through health promotion. In addition, nursing is present in the construction of knowledge and public health policies, which have a direct and indirect impact on the health of transsexual men. This was an exploratory-descriptive study with a qualitative approach, carried out in a trans health clinic in Niterói, Rio de Janeiro, with the participation of twelve transsexual men. As a result, it was noticed that bodily changes allow social visibility and acceptance in a cisheteronormative society. The narratives demonstrate a concern for the ability to “pass” and with security, but, on the other hand, it may be an opportunity to achieve a tranquil life. It was concluded that the objective expectations of transsexual men in relation to cross-sex hormone therapy involve the change in their face, voice and body, and they see this process as a way to obtain satisfaction with their own body. As subjective expectations, there is freedom, respect, and happiness. Nurses can collaborate in the transition process of transsexual men because they have an important role in health education and in the construction of public policies, favoring the minimization of risks and damages in the face of the social vulnerability to which this public is exposed, contributing to the reduction of violence.